Codicology, Islamization, and Qur’an Manuscripts in Southeast Asia: A Structural Mapping of Scholarship - Mursyid, Achmad Yafik; Ali Mat Zin, Aizan; Hamid, Faisal Ahmad Faisal Abdul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
Qur’an manuscripts in Southeast Asia represent both sacred texts and dynamic cultural artefacts. Yet scholarship on these manuscripts has developed in a fragmented and regionally uneven way. This article addresses that problem through a structured analytical mapping of fifty-seven peer-reviewed journal articles published between 2002 and 2024. Drawing on a modified systematic literature analysis grounded in the PICOC framework, the study combines PRISMA-based selection with word-frequency analysis and NVivo-assisted thematic coding to trace publication dynamics, methodological orientations, thematic emphases, and geographic coverage in the field. The results show that approximately seventy-three per cent of the analysed studies have appeared since 2018, signalling a marked rise in academic attention to Qur’an manuscripts in recent years. At the same time, around eighty-five per cent of the corpus focuses on Indonesia and Malaysia, leaving Brunei, southern Thailand, the southern Philippines, and other Malay-Islamic polities largely under-represented. The thematic mapping identifies three interrelated clusters Islamization, Manuscripts, and Studies through which research has approached Southeast Asian mushaf. Rather than offering a narrative overview, the article treats the existing literature as an empirical corpus for conceptual mapping. By identifying recurring patterns and structural blind spots, it proposes an agenda for more geographically inclusive, methodologically diverse, and theoretically self-aware studies that connect philological and codicological analysis with histories of reading, teaching, and Islamization in Southeast Asia.